One‐Pot Synthesis of New Organometallic Compounds with Platinum‐Carbon Bond. Issue 11 (21st January 2020) - Barbanente, Alessandra; Margiotta, Nicola; Pacifico, Concetta; Intini, Francesco P.; Natile, Giovanni
Abstract : Organometallic compounds of platinum containing ortho metalated para‐nitro‐benzamidate or 1‐naphthalene‐methylamine have been prepared by one‐pot synthesis. The para‐nitro‐benzamidate [Pt K 2 C, N‐p NO2 ‐C6 H4 C(O)NH( R, R ‐DACH)] (compound 2 ) was obtained starting from [PtCl2 ( R, R ‐DACH)] and para‐nitro‐benzonitrile, which, in the reaction conditions, hydrolyzes to the corresponding amide and forms the dinuclear intermediate [Pt2 µ‐N, O‐p NO2 ‐C6 H4 C(O)NH2 ( R, R ‐DACH)2 ]SO4 (compound 1· SO4 ) with HH or HT arrangement of the two bridging amidato ligands. Compound 1· SO4, kept at 90 °C for few hours, transforms into 2 . The ortho‐metalated Pt II derivative with 1‐naphthalene‐methylamine [PtCl K 2 C, N‐ C10 H6 CH2 NH2 (DMSO)] (3 ) was obtained by direct reaction of [PtCl2 (DMSO)2 ] with the amine. Unlike compound 2 that has no labile ligands, compound 3 has Cl and DMSO ligands that can be released, allowing the formation of cross‐links with DNA. Oxidation of 3 to the Pt IV counterpart was performed with PhICl2 (compound 4 ). Unexpectedly, although six‐coordinate complexes of Pt IV are considered to be inert, 4 underwent spontaneous isomerization from the mer to the fac isomer. All compounds have been fully characterized by multinuclear NMR spectroscopy, which has enabled complete assignment of all proton resonances. In the case of compound 2, a single‐crystal X‐ray investigation was also performed, showing, with the only exception of the puckered cyclohexane ring, a complete planarity of the complex frame, which could favor an intercalative interaction with DNA. Abstract : σ‐Bonded organometallic platinum compounds containing ortho‐metalated para‐nitro‐benzamidate or 1‐naphthalene‐methylamine with potential antitumor activity have been prepared by one‐pot synthesis. An intermediate dimeric species with a benzamidate ligand bridging two Pt units has been isolated, and it appeared to be a mixture of a head‐to‐head (HH) and a head‐to‐tail (HT) isomers.